Preference-conditioned multi-objective reinforcement learning for train carriage environment control - Boyuan Mu; Chunjun Chen; Lingwei Fei; Yutao Xia; Ji Deng (Building and Environment, 2026)

The pH indicator film based on pomelo rind waste pectin /sodium alginate-purple corn cob extracts combined with deep learning for salmon freshness visualization and detection - Shuyang Sun; Yibing Ding; Chunjun Chen; Chanchan Sun; Xiulian Li; Hansheng Gong; Xiangquan Zeng; Handong Zhao; Jinwang Li; Xinguang Fan (Food Control, 2026)

Responsive packaging that adapted to and regulated physiological metabolic of fruits and vegetables: Mechanism, application and prospects - Chunjun Chen; Yibing Ding; Yucong Feng; Xiulian Li; Chanchan Sun; Fengjun Guo; Xiangquan Zeng; Hansheng Gong; Xinguang Fan (Trends in Food Science & Technology, 2025)

Boosting electroreduction CO2 reduction to formate at ampere level over La doped Bi catalyst - Yichi Zhang; Zijun Zhang; Min Wang; Xia Bai; Yajuan Wang; Yingxuan Liu; Shuaiqiang Jia; Mingyuan He; Chunjun Chen; Haihong Wu; Buxing Han (Sustainable Chemistry and Pharmacy, 2025)

Phosphorus removal in microalgal growth and harvesting using natural flocculant: Influence of microalgal characteristics and phosphorus forms - Jingyi Cao; Donghua Zhao; Chen Chen; Xiaoming Zhu; Yanhao Zheng; Hua Wei; Meifang Hou; Chunjun Li; Siqi Zhang (Bioresource Technology, 2025)

Mechanical behavior and performance evolution of railway ballast track under dynamic stabiliser based on the hybrid MBD-DEM simulation - Jun Fang; Chunfa Zhao; Changsheng Cai; Chunjun Chen; Can Shi; Meng Lin (Transportation Geotechnics, 2024)

Internal pressure fluctuation modelling and passenger pressure comfort analysis of high-speed trains passing through extreme tunnels - Lu Yang; Chunjun Chen; Xiru Wang; Ji Deng; Qin Zheng (Building and Environment, 2024)

Decomposition of harvest residues and soil chemical properties in a Eucalyptus urophylla × grandis plantation under different residue management practices in southern China - Chen Chen; Yilin Weng; Kangting Huang; Xiaolong Chen; Hui Li; Yabin Tang; Lingyue Zhu; Jiachen Wang; Junyu Zhao; Lijun Chen; Lichao Wu; Chunjun Xie; et al. (Forest Ecology and Management, 2023)

Catalpol Mitigates Alzheimer's Disease Progression by Promoting the Expression of Neural Stem Cell Exosomes Released miR-138-5p - Shengxi Meng; Huize Chen; Chunjun Deng; Zeyu Meng (Neurotoxicity Research, 2023)
Alzheimer’s disease (Alzheimer’s disease, AD) is a neurodegenerative disease characterized by senile plaque deposition and neurofibrillary tangles. The pathogenesis of AD is complicated and the drugs used to treat AD are single-targeted drugs, which can only improve or alleviate the symptoms of patients, but cannot delay or prevent the progress of the disease. Because of its ability to act on multiple targets, multiple systems, multiple links, and multiple pathways, Chinese herbal compound prescriptions have shown unique advantages in the research and treatment of AD. Our previous study has demonstrated the protect role of the Chinese medicine Rehmannia in AD. However, the underlying mechanism remains unclear. In the present study, both in vitro and vivo experiments were employed, and we found Catalpol (Ca), the main extract of Rehmannia, could mitigate AD progression both in vitro and in vivo by promoting miR-138-5p level in neural stem cell secreted exosomes